The great stagnation and environmental sustainability: A multidimensional perspective. (4th May 2021) - Cantone, Bernardo; Antonarakis, Alexander S.; Antoniades, Andreas
Abstract: Since the 2008/09 Great Financial Crisis, we have witnessed a prolonged period of persistent global economic slowdown termed the "Great Stagnation". This study examines how this "new normal" is associated with critical environmental dynamics (i.e., biodiversity, water, forest, agriculture, emissions) in areas and groups with different socio‐environmental characteristics (i.e., income groups, continents, forest cover, biome, environmental performance index). Mixed results are shown. For instance, we find a deterioration in terrestrial and marine biodiversity, especially in middle‐ and high‐income countries in Africa and Europe. This includes a reduction in the global fish stock, driven by countries in Africa. In contrast, the Great Stagnation is associated with reductions in PM2.5 (lower‐ and upper mid‐income countries), CH4 emissions (upper mid‐income countries and Europe), forest loss (upper mid‐income countries and Asia), and increases in species habitat index (across most groupings). Our evidence indicates that periods of economic slowdown, such as the great stagnation, on their own cannot ensure a transition to a sustainable socio‐environmental system and may be associated with significant negative environmental effects. Managing our transition to sustainability will require concerted policy efforts across multiple environmental domains, not only on carbon emissions, and during periods of both strong and weak economic growth rates.